Ischemic Gastritis Improved by Supportive Care - Yun Sun Choi; Chan Soo So; Dong Hee Koh; Min Ho Choi; Hyun Joo Jang; Sea Hyub Kae; Jin Lee; Young Hee Choi (Yong Chan Lee, 2017)
Acute extensive ischemic gastritis is an extremely rare disease because the stomach has an abundant submucosal vascular plexus with a dual blood supply from the pancreaticoduodenal and gastroduodenal arteries. Smoking, hypertension, and atherosclerotic vascular diseases can be major risk factors for ischemic gastritis. Acute gastric ischemia presents as an acute abdomen with diarrhea or hematemesis that rapidly progresses to acute peritonitis, irreversible septic shock, and death if untreated. We report a case of acute extensive ischemic gastritis combined with tetraplegia due to cervical myelopathy and extensive atherosclerotic changes of the celiac trunk and abdominal aorta.